2016
DOI: 10.1038/srep31393
|View full text |Cite
|
Sign up to set email alerts
|

U6atac snRNA stem-loop interacts with U12 p65 RNA binding protein and is functionally interchangeable with the U12 apical stem-loop III

Abstract: Formation of catalytic core of the U12-dependent spliceosome involves U6atac and U12 interaction with the 5′ splice site and branch site regions of a U12-dependent intron, respectively. Beyond the formation of intermolecular helix I region between U6atac and U12 snRNAs, several other regions within these RNA molecules are predicted to form stem-loop structures. Our previous work demonstrated that the 3′ stem-loop region of U6atac snRNA contains a U12-dependent spliceosome-specific targeting activity. Here, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 35 publications
1
13
0
Order By: Relevance
“…The model described above does not account for the potential role of the disrupted 65K-U6atac interaction in IGHD. Consistent with a recent report documenting the interaction between 65K C-RRM and the distal stem-loop of U6atac snRNA (Singh et al 2016), our biochemical analysis confirmed that the 65K C-RRM can indeed bind to U6atac, but with approximately threefold reduced affinity compared to U12 snRNA. Furthermore, we documented a similar additional threefold reduction in the U6atac snRNA binding with the P474T mutant and a complete loss of binding with R502X.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The model described above does not account for the potential role of the disrupted 65K-U6atac interaction in IGHD. Consistent with a recent report documenting the interaction between 65K C-RRM and the distal stem-loop of U6atac snRNA (Singh et al 2016), our biochemical analysis confirmed that the 65K C-RRM can indeed bind to U6atac, but with approximately threefold reduced affinity compared to U12 snRNA. Furthermore, we documented a similar additional threefold reduction in the U6atac snRNA binding with the P474T mutant and a complete loss of binding with R502X.…”
Section: Discussionsupporting
confidence: 91%
“…The 3 ′ end of U6atac, which includes the 65K-binding stem-loop, has been demonstrated to play a role in guiding U6atac snRNA to the minor spliceosome (Dietrich et al 2009). Although U6atac snRNA can be pulled down with 65K from HeLa cell lysate (Singh et al 2016), it is not known if the 65K protein associates with the U4atac/U6atac.U5 tri-snRNP or whether, in addition to the A complex, it is present in later spliceosomal complexes. Interestingly, analysis of a zebrafish 65K mutant revealed an accumulation of a slow-migrating complex containing U12, U5, and U6atac snRNAs, leading the authors to suggest an additional role for 65K in the later stages of the splicing process, such as spliceosome disassembly or recycling (Markmiller et al 2014).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The N-terminal portion of the 65K protein binds to the 59K protein and its C-terminal RNA binding domain binds to U12 snRNA Singh et al 2016) (Supplemental Fig. S1B).…”
Section: Introductionmentioning
confidence: 99%